The taxonomic status of Hyla roeschmanni De Grys, 1938 (Anura: Hylidae) - Padial, José M.; Köhler, Jörn; de La Riva, Ignacio (Zootaxa, 2006)
The taxonomic status of Hyla roeschmanni De Grys, 1938 (Anura: Hylidae) is reviewed. We place Hyla roeschmanni as a junior synonym of Hypsiboas raniceps Cope, 1862. Because the holotype of Hyla roeschmanni was destroyed, we designate a neotype from Department Beni, Bolivia, and provide a description of the neotype.